2016
DOI: 10.1093/jac/dkv442
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assessment of the pharmacokinetics of a pleuromutilin, lefamulin, in plasma, soft tissues and pulmonary epithelial lining fluid

Abstract: Lefamulin may be an addition to the therapeutic armamentarium for the treatment of infections. Simultaneous measurements of unbound drug concentration can guide target attainment for future therapeutic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 18 publications
6
53
0
Order By: Relevance
“…The antibacterial spectrum of lefamulin covers the typical Gram-positive and fastidious Gram-negative respiratory pathogens known to cause CABP and atypical pathogens, such as M. pneumoniae (including macrolide-resistant strains), C. pneumoniae, and L. pneumophila (18,19). Pharmacokinetic and pharmacodynamic analyses demonstrated that lefamulin has rapid and predictable penetration into plasma (ϳ1 to 2 g/ml after a single 150-mg intravenous or 600-mg oral dose) (20) and target tissues, such as the epithelial lining fluid in the lung (21), reaching area under the concentration-time curve (AUC):MIC ratios that support the proposed tentative breakpoints of 1 g/ml for S. pneumoniae and 0.5 g/ml for S. aureus (22). This study evaluated the in vitro activity of lefamulin and comparators against a global collection of typical respiratory pathogens that commonly cause CABP, as collected by the SENTRY Antimicrobial Surveillance Program (2015 to 2016).…”
mentioning
confidence: 99%
“…The antibacterial spectrum of lefamulin covers the typical Gram-positive and fastidious Gram-negative respiratory pathogens known to cause CABP and atypical pathogens, such as M. pneumoniae (including macrolide-resistant strains), C. pneumoniae, and L. pneumophila (18,19). Pharmacokinetic and pharmacodynamic analyses demonstrated that lefamulin has rapid and predictable penetration into plasma (ϳ1 to 2 g/ml after a single 150-mg intravenous or 600-mg oral dose) (20) and target tissues, such as the epithelial lining fluid in the lung (21), reaching area under the concentration-time curve (AUC):MIC ratios that support the proposed tentative breakpoints of 1 g/ml for S. pneumoniae and 0.5 g/ml for S. aureus (22). This study evaluated the in vitro activity of lefamulin and comparators against a global collection of typical respiratory pathogens that commonly cause CABP, as collected by the SENTRY Antimicrobial Surveillance Program (2015 to 2016).…”
mentioning
confidence: 99%
“…and Staphylococcus spp., fastidious Gram-negative organisms, such as Haemophilus influenzae, and atypical respiratory pathogens, including Mycoplasma pneumoniae, Chlamydophila pneumoniae, and Legionella pneumophila (14)(15)(16). In addition, in healthy human subjects, lefamulin (unbound protein) demonstrated extensive penetration and accumulation in pulmonary epithelial lining fluid, reaching a median total area under the concentration-time curve from 0 to 12 h (AUC 0 -12 ) of 5.78 g · h/ml and a median maximum concentration of drug in serum (C max ) of ϳ0.7 g/ml after a single 150-mg intravenous infusion over 1 h (17). This study evaluated the in vitro activity of lefamulin against specific serotypes of clinical isolates of Streptococcus pneumoniae.…”
mentioning
confidence: 99%
“…lining fluid, with epithelial lining fluid exposure to lefamulin being 5.7-fold higher than the unbound fraction in plasma [94]. Ιt is 80% protein bound in the serum, has a biologic half-life of 12 hours, and is largely excreted unchanged via the gastrointestinal tract (86%), with the remainder eliminated via the kidneys (14%) [95].…”
Section: Lefamulin Achieves Extensive Penetration and Accumulation Inmentioning
confidence: 99%